2016
DOI: 10.1016/j.ajoc.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Delayed presentation of retained acrylic intraocular lens (IOL) fragment after uncomplicated cataract surgery

Abstract: PurposeTo report a case of delayed presentation of a severed acrylic single-piece intraocular lens (IOL) haptic fragment causing corneal edema after uneventful phacoemulsification surgery.ObservationsAn 85-year-old male presented with inferior corneal decompensation six months after a reportedly uneventful phacoemulsification in his left eye. A distal haptic fragment of an acrylic single-piece posterior chamber intraocular lens was found in the inferior anterior chamber angle. Intraoperative examination reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A distal haptic fragment was seen in the inferior AC angle which originated from the temporal haptic and had a clean, flat surface, suggesting it was severed by a sharp object due to improper implantation. [ 27 ] These cases are often managed in two stages. First stage includes the explanation of the unstable IOL or retained IOL fragments with or without IOL implantation in sulcus if adequate or intrascleral haptic fixation.…”
Section: Etiopathogenesismentioning
confidence: 99%
“…A distal haptic fragment was seen in the inferior AC angle which originated from the temporal haptic and had a clean, flat surface, suggesting it was severed by a sharp object due to improper implantation. [ 27 ] These cases are often managed in two stages. First stage includes the explanation of the unstable IOL or retained IOL fragments with or without IOL implantation in sulcus if adequate or intrascleral haptic fixation.…”
Section: Etiopathogenesismentioning
confidence: 99%
“…It remains unclear whether such microlesions of lens optics are of clinical significance. Trapping or tearing of lens haptics is a complication that occurred with the introduction and wide use of lens shooter systems 9 , 11 , 12 , 13 , 14 , 15 , 16 . Whereas most authors reported this as a casuistic event, Koçluk et al 16 evaluated that trapping of a haptic occurred in his practice in 2.5% of all cases, a surprisingly high incidence.…”
Section: Discussionmentioning
confidence: 99%